Awesome Dog 5000 vs. Mayor Bossypants - Dean, Justin (Awesome Dog 5000 ;, 2020)
"When Awesome Dog's heroics gain media attention, Marty, Skyler, and Ralph find themselves targeted by the narcissistic mayor of Townville"--